2023
DOI: 10.1021/acs.biomac.3c00498
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Phase Behavior, Mechanical Stability, and Protein Reconstitution Properties of Polymer–Lipid Hybrid Vesicles

Abstract: Hybrid vesicles consisting of natural phospholipids and synthetic amphiphilic copolymers have shown remarkable material properties and potential for biotechnology, combining the robustness of polymers with the biocompatibility of phospholipid membranes. To predict and optimize the mixing behavior of lipids and copolymers, as well as understand the interaction between the hybrid membrane and macromolecules like membrane proteins, a comprehensive understanding at the molecular level is essential. This can be ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Except for the systems integrating P(OEGMA- co -LMA)-1, there are also spherical or irregular-shaped vesicles of 20–100 nm with a thinner membrane and a better imaging contrast of 6 nm—still a little larger than that of neat liposomes (≤5 nm) evidencing a hybrid bilayer with a different conformation of the copolymer. 56 58 However, Dao et al (2017) indicated that pure DPPC vesicles were accompanied by a membrane of 6 nm. 51 Reasonably, we could not exclude the scenario that the membrane of these structures corresponds to neat lipid bilayers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the systems integrating P(OEGMA- co -LMA)-1, there are also spherical or irregular-shaped vesicles of 20–100 nm with a thinner membrane and a better imaging contrast of 6 nm—still a little larger than that of neat liposomes (≤5 nm) evidencing a hybrid bilayer with a different conformation of the copolymer. 56 58 However, Dao et al (2017) indicated that pure DPPC vesicles were accompanied by a membrane of 6 nm. 51 Reasonably, we could not exclude the scenario that the membrane of these structures corresponds to neat lipid bilayers.…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that the copolymers were effectively incorporated into the lipid bilayer, and mixed structures were created. 30,51,53,55 Muller et al 56 confirmed the increase of membrane thickness due to different configuration of the copolymer in a lipid-to-polymer ratio-dependent manner. In this study, the membrane thickness does not seem to be influenced by the % weight of the copolymer in the systems.…”
Section: Exploring the Morphology Of Lipid/copolymermentioning
confidence: 94%